Alternatif Penyelesaian Sengketa Pertanahan di Indonesia Melalui Revitalisasi Fungsi Badan Peradilan - Mudjiono Mudjiono (Jurnal Hukum IUS QUIA IUSTUM, 2007)
Inbalancing of land possession will cause conflict. It will distrub the economic and social political stabilization. In order to overcome, the government, through his judicatures, take over all of  the case into the court. Unfortunately, the judgement is unsatisfied his society. Therefore it needs an alternative settlement, the revitalization of function of court.